Customer satisfaction towards service quality of Varsity Mart (V-Mart) at University Utara Malaysia - Ravindran, Thibavany; Hashim, Rushanim (Universiti Utara Malaysia, 2020)
The problem of consumer loyalty and administration quality has twisted out to be one of the principles and essential things thought to consider in all shops. Essentially the administration quality and consumer loyalty offer effect to the business. These two things need to reflect to enhance and keep up their business. Therefore, the objective of this study is to examine the level of customer satisfaction on the service offered by Varsity Mart, UUM, and to examine the relationship between service quality dimensions and customer satisfaction. A total of 100 respondents have participated in this study and the data is analyzed using SPSS. The findings indicate that customer satisfaction has a significant effect on service quality. It recommended improving service quality that which didn’t give an impact on customer satisfaction.